Women in arms production, 1940-1945
1940 1939-1945 "Women in arms production, 1940-1945" [hfr0157], c.1940-1945 Poster showing women working in a Royal Ordnance Factory making 6- pounder guns. 80% of the production staff were women, working 56 hours per week.